Gun Exposure Among Black American Youth Residing in Low-Income Urban Environments. (May 2018) - Quimby, Dakari; Dusing, Catherine Rice; Deane, Kyle; DiClemente, Cara M.; Morency, Mirinda M.; Miller, Kevin M.; Thomas, Andre; Richards, Maryse
Objective: The current study examined the extent of gun exposure, referring to the mere presence of guns in youth's lives, in a sample of Black American adolescents residing in low-income urban neighborhoods. The relationship of gun exposure to internalizing and externalizing outcomes was also explored.Method: Data were collected from a sample of 185 Black American eighth-grade students ( M = 13.58 years old, 59% female).Results: Just under half of the youth reported some type of gun exposure with youth most often exposed to guns outside of the home. Overall gun exposure was related to externalizing but not internalizing symptoms, while knowing someone who owns a gun was related to both externalizing and internalizing symptoms. However, the majority of youth reported exposure to guns in a safe manner (stored locked and unloaded).Conclusions: In addition to gun violence and gun carrying, general gun exposure is a factor that should be accounted for when attempting to address consequences associated with guns.